Non-Contact Capacitive Technique for Biomass Flow Sensing - Rumana Tasnim; Sheroz Khan; Atika Arshad; Molla Rashied Hussein (Institute of Advanced Engineering and Science, 2018)
To facilitate real-time flow measurement, this paper aims to realize biomass flow sensing through electronic non-contact capacitive means. Hardware implementation has been carried out using a modified OP-AMP-based bridge circuit, with one arm made of a standard capacitance while the other arm is made from two specifically designed capacitive electrodes fitted on a piping system sensing biomass flow. The experimental results are targeted to obtain data for given biomass types through a custom-developed biomass flow piping system. Several flow affecting parameters namely: electrodes’ shapes, the location of electrodes on the piping system, biomass material type, and particle size have been considered in obtaining experimental data. Also, the circuit has been simulated to analyze flow sensing behavior for the proposed technique by evaluating the measurement data and assessing conformity between experimentally obtained and simulated data.